Acid-resistant calcium carbonate composition and preparation method and application thereof

Through the wet grinding method of coating the surface of calcium carbonate with silica and polyacrylamide fibers, the problem of easy decomposition of calcium carbonate in acidic media and weak binding force with fibers is solved, which significantly improves its acid resistance and retention rate, and improves the mechanical properties of the paper.

CN119308172BActive Publication Date: 2025-03-21耒阳市百汇粉体有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411854597.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Calcium carbonate is easy to decompose in acidic media, which limits its application in acid papermaking. At the same time, its binding force with fibers is weak, resulting in low retention rate and low raw material utilization rate, which affects the mechanical properties of the paper.

Method used

The silica is firmly and densely coated on the activated calcium carbonate surface by wet grinding, and is tightly coated on the outer surface of the calcium carbonate by using polyacrylamide fibers to improve its acid resistance and binding force with paper fibers.

Benefits of technology

It significantly improves the acid resistance and retention rate of calcium carbonate, avoids the adverse effects of fillers on the mechanical properties of paper, and improves the overall performance of paper.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to an acid-resistant calcium carbonate composition and a preparation method and application thereof, and belongs to the technical field of calcium carbonate preparation. First, sodium hydroxide is used to activate calcium carbonate, and the activation treatment causes a microporous structure to appear on the surface of calcium carbonate, which can quickly adsorb silicon dioxide and improve grinding efficiency, so that silicon dioxide is firmly and densely coated on the surface of calcium carbonate, and the acid resistance of calcium carbonate is significantly improved. Then, grinding and hydrolyzing tetraethyl orthosilicate and grinding polyacrylamide fiber are carried out together, so that silicon dioxide and polyacrylamide fiber are coated on the surface of inner shell silicon dioxide together, so that polyacrylamide fiber is tightly coated on the outer surface of calcium carbonate. The surface of polyacrylamide fiber contains a large number of amide groups, hydroxyl groups and carboxyl groups, which can improve the bonding force between calcium carbonate and paper fiber, thereby improving the compatibility of calcium carbonate and paper fiber, improving the retention rate of calcium carbonate, and avoiding the adverse effects of the addition of filler calcium carbonate on the mechanical properties of paper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of calcium carbonate preparation, and in particular relates to an acid-resistant calcium carbonate composition and a preparation method and application thereof. Background Art

[0002] Calcium carbonate is an important chemical inorganic powder material. Due to its advantages such as low price, wide range of raw materials, and non-toxicity, it is widely used in plastics, rubber, coatings, inks, papermaking and other industries, playing a role in increasing volume and reducing costs, and has extremely high economic value. However, due to its acid-resistant properties, calcium carbonate is easily decomposed in acidic media, which limits its application in acid papermaking. At the same time, the weak binding force between calcium carbonate and fiber makes the retention rate of calcium carbonate in paper low, the utilization rate of raw materials is low, and the mechanical properties of paper will decrease with the increase of the filling amount.

[0003] At present, in order to improve the acid resistance of calcium carbonate, a common method is to use acid-resistant inorganic substances to surface treat calcium carbonate to block the erosion of acidic substances on calcium carbonate. In the prior art, silicon dioxide is often used as an acid-resistant inorganic substance to coat calcium carbonate. The silicon dioxide particles coated on the surface of calcium carbonate are generally nanometer or submicron size. The coating of silicon dioxide reduces the smoothness of the surface of calcium carbonate particles, and the edges and corners are passivated and given to the surface of nanoparticles, thereby maximizing the compatibility and interface bonding between calcium carbonate and the matrix, and significantly improving the acid resistance of calcium carbonate. Chinese patent CN111606345B discloses a method for preparing a light calcium carbonate silicon dioxide composite material, wherein calcium oxide after calcination reacts with water to generate calcium hydroxide, and calcium hydroxide reacts with sodium carbonate to generate light calcium carbonate, and on this basis, sodium silicate solution is reacted with sulfuric acid solution to generate silicon dioxide, thereby obtaining a composite material with calcium carbonate as the core and silicon dioxide coated on the outer layer. In the preparation process of light calcium carbonate, the particles contain a lot of calcium hydroxide, which is easy to react with sulfuric acid in the subsequent silicon coating process after "alkali return", and the generated gas makes the coating effect poor. Therefore, it is necessary to provide an acid-resistant calcium carbonate composition that can solve the above problems. Summary of the invention

[0004] The object of the present invention is to provide an acid-resistant calcium carbonate composition and a preparation method and application thereof, wherein silicon dioxide is firmly and densely coated on the surface of activated calcium carbonate by wet grinding, thereby significantly improving the acid resistance of calcium carbonate. Grinding and hydrolyzing tetraethyl orthosilicate and grinding polyacrylamide fiber are performed together, so that the polyacrylamide fiber is tightly coated on the outer surface of calcium carbonate. Since the surface of polyacrylamide fiber contains a large number of amide groups, hydroxyl groups and carboxyl groups, the bonding force between calcium carbonate and paper fiber can be improved, thereby improving the compatibility of calcium carbonate and paper fiber, improving the retention rate of calcium carbonate, and avoiding the adverse effects of the addition of filler calcium carbonate on the mechanical properties of paper.

[0005] The technical problem to be solved by the present invention is that calcium carbonate is not acid-resistant and is easily decomposed in an acidic medium, which limits its application in acid papermaking. At the same time, the binding force between calcium carbonate and fiber is weak, resulting in a low retention rate of calcium carbonate in paper and a low raw material utilization rate, and the mechanical properties of paper will decrease with the increase of the added amount.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A first aspect of the present invention provides a method for preparing an acid-resistant calcium carbonate composition, comprising the following steps:

[0008] A1. Add calcium carbonate to deionized water, stir evenly at 50-65°C, then add sodium hydroxide, stir for 10-15 minutes, centrifuge, wash and dry to obtain pretreated calcium carbonate;

[0009] Furthermore, in step A1, the usage ratio of calcium carbonate, hot water and sodium hydroxide is (20-23) g: (300-350) mL: (0.16-0.35) g.

[0010] Furthermore, in step A1, the particle size of calcium carbonate is in the range of 5-30 μm.

[0011] A2, adding pretreated calcium carbonate to deionized water to obtain a slurry; tetraethyl orthosilicate, phenol, ethanol and polydimethylsiloxane are mixed and stirred evenly, then added to the slurry and stirred evenly, followed by adding sodium carbonate, and wet grinding for 1-1.5 hours. After grinding, deionized water is added for dilution, and then sodium bicarbonate is added and stirred evenly. The mixture is allowed to settle for 16-19 hours, and the precipitate is separated, washed and dried to obtain silica-coated calcium carbonate;

[0012] Furthermore, in step A2, the usage ratio of pretreated calcium carbonate and deionized water is (10-16) g: (4-6) mL.

[0013] Furthermore, in step A2, the mass ratio of pretreated calcium carbonate, tetraethyl orthosilicate, phenol, ethanol, polydimethylsiloxane and sodium carbonate is (10-16): (4-5.8): (6-7.5): (20-25): (2-3.3): (2-3.2).

[0014] A3. Add silica-coated calcium carbonate into deionized water and stir evenly to obtain a mixed solution; mix tetraethyl orthosilicate, phenol, ethanol and polydimethylsiloxane and stir evenly, add them to the mixed solution and stir evenly, then add the mixed solution of polyacrylamide fiber and deionized water and stir evenly, then add sodium carbonate and continue wet grinding for 1-2 hours. After grinding, add deionized water for dilution, then add sodium bicarbonate and stir evenly, let stand for 24-30 hours, separate the precipitate, wash and dry to obtain acid-resistant calcium carbonate.

[0015] Furthermore, in step A3, the usage ratio of silica-coated calcium carbonate and deionized water is (10-12) g: (3-5) mL.

[0016] Furthermore, in step A3, the mass ratio of silica-coated calcium carbonate, tetraethyl orthosilicate, phenol, ethanol, polydimethylsiloxane and sodium carbonate is (10-12): (1-1.3): (1.5-1.8): (10-15): (1-1.2): (1.1-1.4).

[0017] Furthermore, in step A3, the mass ratio of silica-coated calcium carbonate, polyacrylamide fiber and deionized water is (10-12): (0.6-0.9): (30-50).

[0018] Furthermore, in step A3, the length of the polyacrylamide fiber is 2-8 μm and the diameter is 50-200 nm.

[0019] In the above preparation process, calcium carbonate is first activated with sodium hydroxide. The activation treatment causes a microporous structure to appear on the surface of the calcium carbonate, which can quickly adsorb silicon dioxide, improve grinding efficiency, and accelerate the hydrolysis of tetraethyl orthosilicate, so that silicon dioxide is firmly and densely coated on the surface of calcium carbonate, thereby significantly improving the acid resistance of calcium carbonate.

[0020] In the technical solution of the present invention, a layer of silicon dioxide is first coated on the surface of calcium carbonate, and then grinding and hydrolyzing tetraethyl orthosilicate and grinding polyacrylamide fiber are performed together, so that silicon dioxide and polyacrylamide fiber are coated together on the surface of the inner shell silicon dioxide. The surface of polyacrylamide fiber contains a large number of amide groups, hydroxyl groups and carboxyl groups, which can be connected with silicon dioxide through physical and chemical effects, so that the polyacrylamide fiber is tightly coated on the outer surface of calcium carbonate. In addition, the surface of polyacrylamide fiber contains a large number of amide groups, hydroxyl groups and carboxyl groups, which can improve the binding force between calcium carbonate and paper fiber, thereby improving the compatibility of calcium carbonate and paper fiber, improving the retention rate of calcium carbonate, and avoiding the adverse effects of the addition of filler calcium carbonate on the mechanical properties of paper.

[0021] Furthermore, in step A2, the method for preparing polyacrylamide fiber specifically comprises the following steps:

[0022] B1, adding acrylamide, acrylic acid, hydroxypropyl methacrylate and initiator into a solvent and stirring evenly, reacting at 55-65° C. for 8-12 hours under nitrogen protection, washing with deionized water after the reaction, drying and crushing to obtain an acrylamide copolymer;

[0023] Furthermore, in step B1, the mass ratio of acrylamide, acrylic acid, hydroxypropyl methacrylate, initiator and solvent is (70-80):(10-15):(5-8):(1-3):(200-300).

[0024] Furthermore, in step B1, the solvent is deionized water.

[0025] Furthermore, in step B1, the initiator is ammonium persulfate or potassium persulfate.

[0026] B2. Add acrylamide copolymer into deionized water and stir to dissolve to obtain spinning solution; add the spinning solution into a syringe and use electrostatic spinning technology to prepare polyacrylamide fiber.

[0027] Furthermore, in step B2, the mass fraction of the spinning solution is 2-5%.

[0028] Furthermore, in step B2, the process parameters of the electrospinning technology are: the spinning voltage is 13-18 kV, the flow rate of the spinning solution is 0.8-1.7 mL / h, and the receiving distance is 17-23 cm.

[0029] The second aspect of the present invention provides an acid-resistant calcium carbonate composition prepared by the above preparation method.

[0030] The third aspect of the present invention provides the use of the acid-resistant calcium carbonate composition obtained by the above preparation method in papermaking.

[0031] Beneficial effects of the present invention:

[0032] (1) In the technical solution of the present invention, sodium hydroxide is used to activate calcium carbonate. The activation treatment causes a microporous structure to appear on the surface of calcium carbonate, which can quickly adsorb silicon dioxide, improve grinding efficiency, accelerate the hydrolysis of tetraethyl orthosilicate, and make silicon dioxide firmly and densely coated on the surface of calcium carbonate, thereby significantly improving the acid resistance of calcium carbonate.

[0033] (2) In the technical solution of the present invention, a layer of silica is coated on the surface of calcium carbonate, and then grinding and hydrolyzing tetraethyl orthosilicate and grinding polyacrylamide fibers are performed together, so that silica and polyacrylamide fibers are coated on the surface of the inner shell silica. The surface of polyacrylamide fibers contains a large number of amide groups, hydroxyl groups and carboxyl groups, which can be connected with silica through physical and chemical reactions, so that the polyacrylamide fibers are firmly coated on the outer surface of calcium carbonate.

[0034] (3) In the technical solution of the present invention, the surface of the polyacrylamide fiber contains a large number of amide groups, hydroxyl groups and carboxyl groups, which can improve the binding force between calcium carbonate and paper fibers, thereby improving the compatibility of calcium carbonate with paper fibers, improving the retention rate of calcium carbonate, and avoiding the adverse effects of the addition of filler calcium carbonate on the mechanical properties of paper. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0036] This embodiment provides a method for preparing polyacrylamide fiber, which specifically comprises the following steps:

[0037] B1, add 7g acrylamide, 1g acrylic acid, 0.5g hydroxypropyl methacrylate and 0.1g ammonium persulfate into 20g deionized water and stir evenly, react at 55°C for 8h under nitrogen protection, wash with deionized water after the reaction, dry and grind to obtain acrylamide copolymer;

[0038] B2. Add acrylamide copolymer into deionized water and stir to dissolve to obtain a spinning solution with a mass fraction of 2%; add the spinning solution into a syringe and use electrospinning technology to prepare polyacrylamide fiber. The process parameters of the electrospinning technology are: spinning voltage is 13kV, the flow rate of the spinning solution is 0.8mL / h, and the receiving distance is 20cm. Example 2

[0039] This embodiment provides a method for preparing polyacrylamide fiber, which specifically includes the following steps:

[0040] B1, 7.6g acrylamide, 1.2g acrylic acid, 0.7g hydroxypropyl methacrylate and 0.22g ammonium persulfate were added to 26g deionized water and stirred evenly, and reacted at 60°C for 10h under nitrogen protection. After the reaction, the copolymer was washed with deionized water, dried and crushed to obtain an acrylamide copolymer;

[0041] B2. Add acrylamide copolymer into deionized water and stir to dissolve to obtain a spinning solution with a mass fraction of 3.5%; add the spinning solution into a syringe and use electrospinning technology to prepare polyacrylamide fiber. The process parameters of the electrospinning technology are: spinning voltage is 15kV, the flow rate of the spinning solution is 1.4mL / h, and the receiving distance is 21cm. Example 3

[0042] This embodiment provides a method for preparing polyacrylamide fiber, which specifically includes the following steps:

[0043] B1, 8 g acrylamide, 1.5 g acrylic acid, 0.8 g hydroxypropyl methacrylate and 0.3 g potassium persulfate were added to 30 g deionized water and stirred evenly, and reacted at 65° C. for 12 h under nitrogen protection. After the reaction, the copolymer was washed with deionized water, dried and crushed to obtain an acrylamide copolymer;

[0044] B2. Add acrylamide copolymer into deionized water and stir to dissolve to obtain a spinning solution with a mass fraction of 5%; add the spinning solution into a syringe and use electrospinning technology to prepare polyacrylamide fiber. The process parameters of the electrospinning technology are: spinning voltage is 18kV, the flow rate of the spinning solution is 1.7mL / h, and the receiving distance is 17cm. Example 4

[0045] The preparation method of the acid-resistant calcium carbonate composition comprises the following steps:

[0046] A1. Add 20 g of calcium carbonate with an average particle size of 5 μm into 300 mL of deionized water, stir evenly at 50° C., then add 0.16 g of sodium hydroxide, stir for 10 min, centrifuge, wash, and dry to obtain pretreated calcium carbonate;

[0047] A2, 10g of pretreated calcium carbonate was added to 4mL of deionized water to obtain a slurry; 4g of tetraethyl orthosilicate, 6g of phenol, 20g of ethanol and 2g of polydimethylsiloxane were mixed and stirred evenly, then added to the slurry and stirred evenly, followed by adding 2g of sodium carbonate and wet grinding for 1h. After grinding, 2.5 times the volume of deionized water was added for dilution, and then 12g of sodium bicarbonate was added and stirred evenly. The mixture was allowed to settle for 16h, and the precipitate was separated, washed and dried to obtain silica-coated calcium carbonate;

[0048] A3. Add 10g of silica-coated calcium carbonate to 3mL of deionized water and stir to obtain a mixed solution; mix 1g of tetraethyl orthosilicate, 1.5g of phenol, 10g of ethanol and 1g of polydimethylsiloxane and stir evenly, add to the mixed solution and stir evenly, then add 0.6g of polyacrylamide fiber (the average length of the polyacrylamide fiber is 2μm and the average diameter is 83nm) prepared in Example 2 and 30g of deionized water and stir evenly, then add 1.1g of sodium carbonate and continue wet grinding for 1h. After grinding, add 3 times the volume of deionized water for dilution, then add 8g of sodium bicarbonate and stir evenly, let stand for 24h, separate the precipitate, wash and dry to obtain acid-resistant calcium carbonate. Example 5

[0049] The preparation method of the acid-resistant calcium carbonate composition comprises the following steps:

[0050] A1. Add 22 g of calcium carbonate with an average particle size of 18 μm to 320 mL of deionized water, stir evenly at 55° C., then add 0.128 g of sodium hydroxide, stir for 15 min, centrifuge, wash, and dry to obtain pretreated calcium carbonate;

[0051] A2, 13g of pretreated calcium carbonate was added to 5mL of deionized water to obtain a slurry; 5.2g of tetraethyl orthosilicate, 6.8g of phenol, 23g of ethanol and 2.7g of polydimethylsiloxane were mixed and stirred evenly, then added to the slurry and stirred evenly, followed by adding 2.6g of sodium carbonate, and wet grinding was performed for 1.5h. After the grinding was completed, 2.5 times the volume of deionized water was added for dilution, and then 12g of sodium bicarbonate was added and stirred evenly, and the sedimentation was allowed to settle for 17h, and the precipitate was separated, washed and dried to obtain silica-coated calcium carbonate;

[0052] A3. 11 g of silica-coated calcium carbonate was added to 4 mL of deionized water and stirred to obtain a mixed solution; 1.1 g of tetraethyl orthosilicate, 1.6 g of phenol, 13 g of ethanol and 1.1 g of polydimethylsiloxane were mixed and stirred, and added to the mixed solution and stirred, then 0.78 g of polyacrylamide fiber (the average length of the polyacrylamide fiber is 5.6 μm and the average diameter is 126 nm) prepared in Example 2 and 40 g of deionized water were added and stirred, then 1.25 g of sodium carbonate was added, and wet grinding was continued for 1.5 h. After grinding, 3 times the volume of deionized water was added for dilution, and then 8 g of sodium bicarbonate was added and stirred, and the mixture was allowed to stand for 26 h. The precipitate was separated, washed and dried to obtain acid-resistant calcium carbonate. Example 6

[0053] The preparation method of the acid-resistant calcium carbonate composition comprises the following steps:

[0054] A1. Add 23 g of calcium carbonate with an average particle size of 29 μm to 350 mL of deionized water, stir evenly at 65° C., then add 0.35 g of sodium hydroxide, stir for 15 min, centrifuge, wash, and dry to obtain pretreated calcium carbonate;

[0055] A2, 16g of pretreated calcium carbonate was added to 6mL of deionized water to obtain a slurry; 5.8g of tetraethyl orthosilicate, 7.5g of phenol, 25g of ethanol and 3.3g of polydimethylsiloxane were mixed and stirred evenly, then added to the slurry and stirred evenly, followed by adding 3.2g of sodium carbonate, and wet grinding was performed for 1.5h. After the grinding was completed, 2.5 times the volume of deionized water was added for dilution, and then 12g of sodium bicarbonate was added and stirred evenly, and the mixture was settled for 19h, and the precipitate was separated, washed and dried to obtain silica-coated calcium carbonate;

[0056] A3. 12 g of silica-coated calcium carbonate was added to 5 mL of deionized water and stirred to obtain a mixed solution; 1.3 g of tetraethyl orthosilicate, 1.8 g of phenol, 15 g of ethanol and 1.2 g of polydimethylsiloxane were mixed and stirred, and added to the mixed solution and stirred, then 0.9 g of polyacrylamide fiber (the average length of the polyacrylamide fiber is 7.8 μm and the average diameter is 194 nm) prepared in Example 2 and 50 g of deionized water were added and stirred, then 1.4 g of sodium carbonate was added, and wet grinding was continued for 2 h. After grinding, 3 times the volume of deionized water was added for dilution, and then 8 g of sodium bicarbonate was added and stirred, and the mixture was allowed to stand for 30 h. The precipitate was separated, washed and dried to obtain acid-resistant calcium carbonate.

[0057] Comparative Example 1

[0058] Compared with Example 5, step A3 was not performed in Comparative Example 1, and the other steps and raw materials were the same as those in Example 5.

[0059] Comparative Example 2

[0060] Compared with Example 5, the calcium carbonate in Comparative Example 2 was not pretreated with sodium hydroxide, and the other steps and raw materials were the same as those in Example 5.

[0061] Comparative Example 3

[0062] Compared with Example 5, in Comparative Example 3, during step A3, only polyacrylamide fiber is added for grinding, that is, the surface of the silica-coated calcium carbonate obtained in step A2 is only coated with polyacrylamide fiber, and the other steps and raw materials are the same as those in Example 5.

[0063] Performance Testing

[0064] (1) Acid solubility: 125 mL of potassium hydrogen phthalate and 97 mL of sodium hydroxide solution (both at a concentration of 0.1 mol / L) were weighed and fixed to 500 mL to prepare a buffer solution (pH = 5.5). 0.2 g of the products of Examples 4-6 and Comparative Examples 1-3 were respectively placed in 100 mL of the buffer solution and soaked for 6 h. After filtering, the Ca content in the filtrate was determined by titration. 2+ The mass concentration of 1 / M 0 )×100%,M 1 is the mass of calcium carbonate dissolved, M 0 is the mass of calcium carbonate before dissolution.

[0065] (2) Tensile strength and retention rate: Poplar chemimechanical pulp and bamboo chemimechanical pulp were mixed and beaten at an absolute dry weight ratio of 3:1, with a beating degree of 38°SR, and 30% of the product fillers of Examples 4-6 and Comparative Examples 1-3 were added, and a Buchner funnel was used to make a paper with a basis weight of about 100 g / m 2 The pulp sheet is placed in an oven and dried at a temperature not exceeding 60°C to form a paper sheet; the paper strength is tested using a tensile strength tester and the filler ash content is measured in a muffle furnace to calculate the retention rate.

[0066] As shown in the following table:

[0067] project Acid solubility (%) Tensile index (N·m / g) Retention rate (%) Example 4 14.9 32.2 97.1 Example 5 14.2 33.4 98.3 Example 6 14.5 32.8 97.6 Comparative Example 1 16.1 13.8 85.9 Comparative Example 2 15.7 32.1 97.3 Comparative Example 3 15.5 27.6 93.9

[0068] It can be seen from the above table data that the calcium carbonate composition prepared by the present invention has excellent acid resistance, and the paper obtained by adding it as a filler to paper has good tensile strength and a high filler retention rate. It can be seen from the data of Comparative Example 5 and Comparative Example 1 that since the surface of the silica-coated calcium carbonate is not coated with silica and polyacrylamide fiber, the compatibility of the calcium carbonate composition with the paper fiber decreases, thereby causing the tensile strength and filler retention rate of the paper to decrease. It can be seen from the data of Comparative Example 5 and Comparative Example 2 that since the calcium carbonate is not pretreated with sodium hydroxide, the acid solubility rate decreases. It can be seen from the data of Comparative Example 5 and Comparative Example 3 that since the surface of the silica-coated calcium carbonate is only coated with polyacrylamide fiber, the polyacrylamide fiber and silica are not co-coated on the surface of the silica-coated calcium carbonate, the acid resistance of the calcium carbonate composition decreases, and the tensile strength and filler retention rate of the obtained paper also decrease.

[0069] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0070] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. The preparation method of the acid-resistant calcium carbonate composition is characterized in that: The following steps are involved: A1. Add calcium carbonate to deionized water, stir evenly at 50-65°C, then add sodium hydroxide, stir for 10-15 minutes, centrifuge, wash and dry to obtain pretreated calcium carbonate; A2, adding pretreated calcium carbonate to deionized water to obtain a slurry; tetraethyl orthosilicate, phenol, ethanol and polydimethylsiloxane are mixed and stirred evenly, then added to the slurry and stirred evenly, followed by adding sodium carbonate, and wet grinding for 1-1.5 hours. After grinding, deionized water is added for dilution, and then sodium bicarbonate is added and stirred evenly. The mixture is allowed to settle for 16-19 hours, and the precipitate is separated, washed and dried to obtain silica-coated calcium carbonate; A3. Add silica-coated calcium carbonate into deionized water and stir evenly to obtain a mixed solution; mix tetraethyl orthosilicate, phenol, ethanol and polydimethylsiloxane and stir evenly, add them to the mixed solution and stir evenly, then add the mixed solution of polyacrylamide fiber and deionized water and stir evenly, then add sodium carbonate and continue wet grinding for 1-2 hours. After grinding, add deionized water for dilution, then add sodium bicarbonate and stir evenly, let stand for 24-30 hours, separate the precipitate, wash and dry to obtain acid-resistant calcium carbonate.

2. The method for preparing an acid-resistant calcium carbonate composition according to claim 1, wherein: In the step A1, the usage ratio of calcium carbonate, hot water and sodium hydroxide is (20-23) g: (300-350) mL: (0.16-0.35) g.

3. The preparation method of the acid-resistant calcium carbonate composition according to claim 1, wherein: In the step A2, the mass ratio of pretreated calcium carbonate, tetraethyl orthosilicate, phenol, ethanol, polydimethylsiloxane and sodium carbonate is (10-16): (4-5.8): (6-7.5): (20-25): (2-3.3): (2-3.2).

4. The preparation method of the acid-resistant calcium carbonate composition according to claim 1, wherein: In the step A3, the mass ratio of silica-coated calcium carbonate, tetraethyl orthosilicate, phenol, ethanol, polydimethylsiloxane and sodium carbonate is (10-12): (1-1.3): (1.5-1.8): (10-15): (1-1.2): (1.1-1.4).

5. The preparation method of the acid-resistant calcium carbonate composition according to claim 1, wherein: In the step A3, the mass ratio of silica-coated calcium carbonate, polyacrylamide fiber and deionized water is (10-12): (0.6-0.9): (30-50).

6. The method for preparing an acid-resistant calcium carbonate composition according to claim 1, wherein: In the step A3, the length of the polyacrylamide fiber is 2-8 μm and the diameter is 50-200 nm.

7. The preparation method of the acid-resistant calcium carbonate composition according to claim 1, wherein: In step A2, the method for preparing polyacrylamide fiber specifically comprises the following steps: B1, adding acrylamide, acrylic acid, hydroxypropyl methacrylate and initiator into a solvent and stirring evenly, reacting at 55-65° C. for 8-12 hours under nitrogen protection, washing with deionized water after the reaction, drying and crushing to obtain an acrylamide copolymer; B2. Add acrylamide copolymer into deionized water and stir to dissolve to obtain spinning solution; add the spinning solution into a syringe and use electrostatic spinning technology to prepare polyacrylamide fiber.

8. The method for preparing the acid-resistant calcium carbonate composition according to claim 7, wherein: In the step B1, the mass ratio of acrylamide, acrylic acid, hydroxypropyl methacrylate, initiator and solvent is (70-80): (10-15): (5-8): (1-3): (200-300); in the step B2, the process parameters of the electrospinning technology are: the spinning voltage is 13-18 kV, the flow rate of the spinning solution is 0.8-1.7 mL / h, and the receiving distance is 17-23 cm.

9. An acid-resistant calcium carbonate composition obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the acid-resistant calcium carbonate composition obtained by the preparation method according to any one of claims 1 to 8 in papermaking.

Citation Information

Patent Citations

  • A method for preparing a lightweight calcium carbonate and silica composite material

    CN111606345B

  • High-dispersity calcium powder and preparation method thereof

    CN117447856A

  • PROCESS FOR MAKING PAPER AND FILLER CONGLOMERATE USED THEREOF

    DE2632350A1